Factors influencing work stress among nurses: women and baby centre ward & general ward KPJ Johor Specialist Hospital / Nur Jannah Abu Bakar - Abu Bakar, Nur Jannah (Faculty of Business and Management, 2020)
Currently, in today’s society, our life tends to fraught with troubles, deadlines, frustration, demands and many more. Stress has been nominated as part of life. We live with it, deal with it and more importantly worry about it. In fact, our way of life which we live as well as our job might lead to a great deal of stress due to an individual likely experience different level of stress. Remarkably, work-related stress can be identified as the major worst situation an individual encounter along their working career, which might cause them to suffer from emotional and physical anguish. In certain circumstances, work-related stress that occurs in prolonged period would definitely result in some serious and fatal health issue. James (2009) clearly stated that “The greatest weapon against stress is our ability to choose one thought over another”. As a matter a fact, the profession of nursing is full of stress and challenges as nurse plays a crucial role in improving the patient’s health and well-being which made them highly vulnerable to develop work-related stress. The researcher has been conducted a research on factors influencing work stress among women and baby centre ward as well as general ward nurses at KPJ Johor Specialist Hospital. This study is conducted to investigate if excessive workload factor, poor work environment factor, lack of social support factor and shortage of manpower factor will influence work stress among women and baby centre ward as well as general ward nurses at KPJ Johor Specialist Hospital. As for sampling method, researcher have been decided to use cluster sampling in order to distribute a questionnaire survey to respondent. For this research, researcher decided to select a total of 80 nurses as a sample which taken from Women and Baby Centre ward and General Ward as the respondent. For the questionnaire design, researcher use Linkert Scale as the method is simple to administer. The nurses were asked to rate the questionnaire survey by choosing from four alternatives: strongly agree (4), agree (3), disagree (2) and strongly disagree (1). The instrument used by researcher for data collection is SPSS software. Other than that, for data analysis and findings, researcher used frequency analysis, descriptive analysis, reliability analysis, correlation analysis and multiple regression analysis. As for multiple regression analysis, the researcher discovers that excessive workload factor (2.5%) and shortage of manpower factor (0.8%) is significant because the p-value for both factors below than 0.05 percent significant levels. Thus, excessive workload and shortage of manpower positively related to work stress among nurses. While the poor work environment factor and lack of social support factor is not significant as the p-value of these factors above 0.05 percent significant levels. Hence, poor work environment and shortage of manpower are not related to work stress among women and baby centre ward as well as general ward nurses at KPJ Johor Specialist Hospital.